HUBUNGAN TINGKAT KECEMASAN TERHADAP PENGELUARAN KOLOSTRUM PADA IBU POST SECTIO CAESAREA DI RSUD MEURAXA KOTA BANDA ACEH - T. Murhadi; Siti Hajar; Elviana (Jurnal Medicare, 2025)
The production of breast milk in mothers who undergo Caesarean section is influenced by several factors, including psychological ones such as anxiety. In Indonesia, the rate of exclusive breastfeeding for infants aged 0–6 months is 72.07%, and the tendency to give colostrum is 85.4%. One of the factors affecting colostrum secretion is the use of medication during Caesarean procedures. This study aimed to examine the relationship between anxiety levels and colostrum secretion in post-Caesarean section mothers at Meuraxa Regional Hospital, Banda Aceh. The study used an analytical method with a cross-sectional approach. The population consisted of all post-Caesarean section mothers treated in the maternity ward. A total of 36 respondents were selected using accidental sampling. The results showed that 75% of mothers who experienced anxiety had inhibited colostrum secretion, while 16.7% of those who were not anxious experienced smooth colostrum flow. Statistical analysis showed a significant relationship (p-value = 0.000). In conclusion, there is a significant association between anxiety and colostrum secretion in post-Caesarean mothers. These findings can help improve the quality of maternal care and guide midwives in managing postpartum care for mothers after Caesarean delivery.